Ocorrência de novos espécimens de Taeniopteris na Bacia Carbonífera do Douro (Estefaniano C inferior) [Gzheliano inferior],NW de Portugal - P. Correia (2010)
Contribution and stratigraphic implications discussion of new specimens of Taeniopteris (Taeniopteris jejunata, Taeniopteris bertrandiana and Taeniopteris sp. nov. (two species ?) found in the São Pedro da Cova region (Gondomar), Douro Carboniferous Basin (lower Stephanian C) [lower Gzhelian]